1999
DOI: 10.1002/(sici)1097-0088(19991130)19:14<1517::aid-joc437>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

North American snow extent: 1900–1994

Abstract: Historical fluctuations of North American snow extent from November through March are reconstructed back to 1900 using a combination of satellite and station observations. Using results of principal components analyses (PCA) from a companion study (Frei, A. and Robinson, D.A. Int. J. Climatol., this volume), simple and multiple linear regression models are used to take advantage of the spatial coverage of satellite observations and the temporal extent of station observations. This analysis more than triples th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 2 publications
1
15
0
Order By: Relevance
“…These periods will be used in the following discussion to better emphasize the effect of snow cover and soil moisture trends on SAT and GST temperatures in the last part of the simulation. Values are realistic in comparison to observations (Brown and Goodison, 1996;Frei et al, 1999;Brown, 2000;Brown et al, 2003) and interestingly they show increases (decreases) in snow depth over the northern (middle) latitudes since the simulated LIA to the end of the 20th century. 3 allows the discussion to be extended to the possible influence of soil moisture on air-ground temperature differences.…”
Section: Boreholes In the Gcm Surrogate Realitymentioning
confidence: 57%
“…These periods will be used in the following discussion to better emphasize the effect of snow cover and soil moisture trends on SAT and GST temperatures in the last part of the simulation. Values are realistic in comparison to observations (Brown and Goodison, 1996;Frei et al, 1999;Brown, 2000;Brown et al, 2003) and interestingly they show increases (decreases) in snow depth over the northern (middle) latitudes since the simulated LIA to the end of the 20th century. 3 allows the discussion to be extended to the possible influence of soil moisture on air-ground temperature differences.…”
Section: Boreholes In the Gcm Surrogate Realitymentioning
confidence: 57%
“…The NAO, the Eurasian Type 1 (EU1), and the Siberian pattern (SIB) were three different telelconnections which emerged as significant in snow cover variability across the entire Eurasian continent (Clark et al, 1999). In a similar study over North America, Frei et al (1999) found that a 20-30°longitudinal shift to the west, of the mean North American ridge, led to substantial positive snow cover anomalies over western regions of the continent. Over eastern North America, snow cover variability was associated with a bipolar oscillation in 500 hPa heights between southern Greenland and the mid-latitude North Atlantic.…”
Section: Previous Researchmentioning
confidence: 98%
“…Numerous subcontinental scale studies of European snow cover have been carried out with relationships between snow cover variability and phase of the North Atlantic Oscillation (hereafter called the NAO) pattern being a persistent theme. This study considers the area of Europe west of the Ural Mountains and is unique as areas of 'active' snow cover (Clark et al, 1999;Frei et al, 1999) are present throughout 65% of the region. Analysis of snow cover using the satellite dataset has been conducted on both hemispheric and continental scales previously; however, the area of Europe west of the Ural Mountains has never been isolated for intense investigation.…”
Section: The Significance Of Snow Covermentioning
confidence: 99%
“…In the Southern Hemisphere, outside of Antarctica and its surrounding ice shelves and sea ice, snow is generally limited to smaller regions such as the Andes, Patagonia and the southern Alps of New Zealand (Foster et al, 2008). On decadal time scales, snow variations over Northern Hemisphere lands have also been considerable (Barry et al, 1995;Brown, 2000;Brown and Braaten, 1998;Derksen et al, 2004;Frei et al, 1999;Mote, 2006;Mote et al, 2005;Ye et al, 1998), with declines in spring associated with warmer conditions (Brown et al, 2010;Groisman et al, 1994;IPCC, 2007;Leathers and Robinson, 1993). Recent reports on changes in the Arctic environment cite snow as one of the critical variables (ACIA, 2004;AMAP, 2011).…”
Section: Introductionmentioning
confidence: 99%